Bridging the Interfacial Contact for Improved Stability and Efficiency of Inverted Perovskite Solar Cells. Issue 24 (17th May 2022) - Huang, Yulan; Liu, Tanghao; Li, Dongyang; Lian, Qing; Wang, Yun; Wang, Guoliang; Mi, Guojun; Zhou, Yuanyuan; Amini, Abbas; Xu, Baomin; Tang, Zikang; Cheng, Chun; et al.
Abstract: Inverted perovskite solar cells (PSCs) have received widespread attention due to their facile fabrication and wide applications. However, their power conversion efficiency (PCE) is reported lower than that of regular PSCs because of the undesirable interfacial contact between perovskite and the hydrophobic hole transport layer (HTL). Here, an interface regulation strategy is proposed to overcome this limitation. A small molecule ([2‐(9H‐carbazol‐9‐yl) ethyl] phosphonic acid, abbreviated as 2P), composed of carbazole and phosphonic acid groups, is inserted between perovskite and HTL. Morphological characterization and theoretical calculation reveal that perovskite bonds stronger on 2P‐modified HTL than on pristine HTL. The improved interfacial contact facilitates hole extraction and retards degradation. Upon the incorporation of 2P, inverted PSCs deliver a high PCE of over 22% with superior stability, keeping 84.6% of initial efficiency after 7200 h storage under an ambient atmosphere with a relative humidity of ≈30–40%. This strategy provides a simple and efficient way to boost the performance of inverted PSCs. Abstract : [2‐(9H‐carbazol‐9‐yl) ethyl] phosphonic acid (2P) is introduced to modify the surface of the hole‐transport layer (HTL). 2P benefits the perovskite growth and interfacial contact. Moreover, 2P‐modified HTL shows better energy‐level alignment with perovskite. The 2P‐incorporated inverted perovskite solar cell delivers a high efficiency of 22.17% and keeps stable under ambient atmosphere (RH: ≈30–40%) without encapsulation for 7200 h.